2013
DOI: 10.1590/s1415-47572013000100014
|View full text |Cite
|
Sign up to set email alerts
|

The presence of sboA and spaS genes and antimicrobial peptides subtilosin A and subtilin among Bacillus strains of the Amazon basin

Abstract: This report demonstrates the usefulness of PCR for the genes spaS and sboA as a means of identifying Bacillus strains with a potential to produce subtilin and subtilosin A. One collection strain and five Bacillus spp. isolated from aquatic environments in the Amazon basin were screened by PCR using primers for sboA and spaS designed specifically for this study. The sequences of the PCR products showed elevated homology with previously described spaS and sboA genes. Antimicrobial peptides were isolated from cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…For example, it has been reported that genes for antimicrobial dipeptides, such as bacilysin, as well as genes for another lantibiotic very active against gram positive bacteria, subtilin and subtilosin A, were present in 93% of the strains ( Harwood et al, 2018 ). Moreover, it is known that the strains used in this study have the ability to produce these antibacterial molecules ( Parisot et al, 2008 ; Fickers, 2012 ; Velho et al, 2013 ). The main problem with these peptides is their low stability, in fact they can degrade quickly in the culture medium of B. subtilis or during the purification process ( Kuboi et al, 1994 ).…”
Section: Resultsmentioning
confidence: 99%
“…For example, it has been reported that genes for antimicrobial dipeptides, such as bacilysin, as well as genes for another lantibiotic very active against gram positive bacteria, subtilin and subtilosin A, were present in 93% of the strains ( Harwood et al, 2018 ). Moreover, it is known that the strains used in this study have the ability to produce these antibacterial molecules ( Parisot et al, 2008 ; Fickers, 2012 ; Velho et al, 2013 ). The main problem with these peptides is their low stability, in fact they can degrade quickly in the culture medium of B. subtilis or during the purification process ( Kuboi et al, 1994 ).…”
Section: Resultsmentioning
confidence: 99%
“…Baindara et al (41) characterized two antimicrobial peptides produced by a B. subtilis strain, which showed antagonistic properties against Gram-positive bacteria, including S. aureus and Listeria monocytogenes. Other Bacillus species have been reported to produce bacteriocins and biosurfactants (42,43); the bacteriocins inhibited the growth of a large range of Gram-positive and Gramnegative bacteria. Bacillus subtilis E0g strongly inhibited most Gram-positive targets, including C. maltaromaticum D8c, B. thermosphacta A0b, Bacillus sp.…”
Section: Discussionmentioning
confidence: 99%
“…The sporulation killing factor short as SKF is a 26 amino acids sactipeptide ( Figure 1 ) that plays a key role during the strain's sporulation (Gonzalez-Pastor et al, 2003 ; Velho et al, 2013 ). SKF contains a thioether bond cross-link between Cys4 and Met12, a disulfide bond cross-link between Cys1 and Cys16, and a head-to-tail cyclic architecture by an amide bond.…”
Section: Biosynthesis Of Sactipeptidesmentioning
confidence: 99%
“…The skf gene cluster is encoding the enzymes for SKF biosynthesis. It comprised of a precursor gene skfA , post-modification genes skfB (rSAM enzyme), skfC (putative protease), skfH (putative thioredoxin), skfE/skfF for export/resistance, and skfG for unknown function ( Figure 2 ) (Velho et al, 2013 ). Like AlbA, SkfB is the functional subclass rSAM enzyme responsible for sactionine formation (Fluhe et al, 2013 ).…”
Section: Biosynthesis Of Sactipeptidesmentioning
confidence: 99%